(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the content and significance of the concept of family in religious texts on the example of the work of Sheikh Muhammad Sadiq Muhammad Yusuf "Bakhtiyor Oila". The study highlights the role of the family in society and human life, views on marital relations and upbringing of children in Islamic sources. modern family relations.